2000
DOI: 10.1093/ajcn/72.1.168
|View full text |Cite
|
Sign up to set email alerts
|

A threshold for low-protein-diet–induced elevations in parathyroid hormone

Abstract: Background:We reported previously that lowering dietary protein intake in young healthy women to 0.7 g/kg depressed intestinal calcium absorption and was accompanied by elevations in parathyroid hormone (PTH). Moderate amounts of dietary protein (1.0 g/kg) did not appear to perturb calcium homeostasis. Objective: The purpose of this study was to evaluate the effect of graded intakes of dietary protein (0.7, 0.8, 0.9, and 1.0 g/kg) on calcium homeostasis. Design: The experiment consisted of 2 wk of a well-balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 17 publications
2
39
0
Order By: Relevance
“…Conversely, there is evidence that a low-protein diet might decrease Ca absorption. Kerstetter et al showed that short-term intake of a moderately low-protein (0.7 g/kg) diet decreased urinary Ca excretion and was accompanied by secondary hyperparathyroidism (as a consequence of reduced Ca absorption), while the levels of 5 0.9 g/kg with the same intake of Ca (800 mg/day) did not interfere with Ca absorption in healthy young women (Kerstetter et al, 1997(Kerstetter et al, , 2000a. Findings from the epidemiological studies imply that a low-protein diet may adversely affect bone and significantly contribute to reduced BMD (Hannan et al, 2000;Kerstetter et al, 2000b).…”
Section: Confounding Factorsmentioning
confidence: 99%
“…Conversely, there is evidence that a low-protein diet might decrease Ca absorption. Kerstetter et al showed that short-term intake of a moderately low-protein (0.7 g/kg) diet decreased urinary Ca excretion and was accompanied by secondary hyperparathyroidism (as a consequence of reduced Ca absorption), while the levels of 5 0.9 g/kg with the same intake of Ca (800 mg/day) did not interfere with Ca absorption in healthy young women (Kerstetter et al, 1997(Kerstetter et al, , 2000a. Findings from the epidemiological studies imply that a low-protein diet may adversely affect bone and significantly contribute to reduced BMD (Hannan et al, 2000;Kerstetter et al, 2000b).…”
Section: Confounding Factorsmentioning
confidence: 99%
“…Thus, the trough of the amino acid rhythm coincides with the peak of the PTH rhythm -the predicted behaviour for an acute inhibitor of PTH secretion (Figure 7). The circadian rhythm for plasma amino acids appears to be exaggerated in individuals on high protein diets but is attenuated in individuals on low protein diets (Fernstrom et al, 1979) -a circumstance in which PTH levels are mark-L-Amino acid sensing AD Conigrave et al edly elevated (Kerstetter et al, 1997(Kerstetter et al, , 2000b …”
Section: Is the Car A Target For The Toxicity Of Aromatic L-amino Acimentioning
confidence: 99%
“…Amino acid sensing mechanisms, especially for aromatic L-amino acids, also have a significant impact on digestion and absorption by the digestive tract. Finally, an amino acid sensing mechanism would appear to explain how protein and calcium metabolism are linked so that high protein intake promotes urinary calcium excretion (Allen et al, 1979;Johnson et al, 1970;Kerstetter & Allen, 1994; Figure 1) and low protein intake induces a state of secondary hyperparathyroidism (Kerstetter et al, 1997;Kerstetter et al, 2000b; Figure 2). …”
mentioning
confidence: 99%
“…Recently, it has been shown that a high protein intake increases calcium bioavailability, making less calcium available for binding to fat in the intestine. [30][31][32][33] In the investigation by Jacobsen et al, 19 the significant effects on faecal fat excretion were only observed in the high-calcium, low-protein diets. The faecal energy content of the present investigation is comparable to the condition in the study of Jacobsen with a high protein content (that is, 23%), in which they did not observe any effects of increasing calcium intake on fat excretion.…”
Section: Discussionmentioning
confidence: 96%